2022
DOI: 10.3390/ijerph191610267
|View full text |Cite
|
Sign up to set email alerts
|

Injury Incidence Increases after COVID-19 Infection: A Case Study with a Male Professional Football Team

Abstract: Background: The SARS-CoV-2 virus disease has caused numerous changes in sports routines in the last two years, showing the influence on an increase in sports injuries. The aim of this study was to prospectively analyze the incidence and characteristics of injuries in male professional football players diagnosed with COVID-19 when they return to play after recovering from this illness. Methods: Injury characteristics of professional male football players were recorded for the 2020–2021 season following the inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…The risk of injury is also inevitable because of the increased training time during the pandemic, and the cluster of topics related to injury experiences and concerns may also reflect the temporal nature of the pandemic ( Schuttler et al, 2022 ). In addition, clusters containing keywords about returning from injury and athletes returning after the pandemic are not conclusions based on experiments or surveys but rather topics that can be expected to be the subject of further research ( Ross et al, 2021 ; Maestro et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…The risk of injury is also inevitable because of the increased training time during the pandemic, and the cluster of topics related to injury experiences and concerns may also reflect the temporal nature of the pandemic ( Schuttler et al, 2022 ). In addition, clusters containing keywords about returning from injury and athletes returning after the pandemic are not conclusions based on experiments or surveys but rather topics that can be expected to be the subject of further research ( Ross et al, 2021 ; Maestro et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our results confirm the findings of other studies [ 23 , 51 , 65 ], even if our study has more exhaustive collecting modalities, a bigger sample size, and a higher number of events recorded. Other similar research explores this situation in other major football European championships, demonstrating how this is a new, hot, and widespread topic in the scientific literature: Wezenbeek et al [ 26 ] reported a five times higher risk of developing a muscle strain after COVID-19 in Belgian professional footballers; Mannino et al [ 22 ] showed an increase in injuries in the pandemic-related English Premier Leagues season; Maestro et al [ 19 ] highlighted a doubled risk of muscle injuries after COVID-19 in Spanish football players; and Seshadiri et al [ 25 ] shared a similar worrying scenario in German Bundesliga.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies tried to investigate how SARS-CoV-2 infection could affect the performance of athletes and, at the same time, put forward the hypothesis that COVID-19 could increase the risk of musculoskeletal injuries [ 5 , 9 , 10 , 15 , 16 , 17 , 18 , 19 ]. Indeed, muscle injuries still represent the first cause of injuries in football, accounting for a huge amount of missed matches for the players [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Response: The Bundesliga study [ 8 ] did not include analysis for the years following the pandemic. Another study [ 9 ] looked at injury incidence as related to COVID-19 infection. One study [ 10 ] looked at a 41-day period of injury epidemiology for 3 periods, 2 of which were after the lockdown but still within the 2020 time period.…”
Section: Anonymous [ 7 ]mentioning
confidence: 99%